Flipped Classroom : Model Pembelajaran untuk Mencapai Kecakapan Abad 21 Sesuai Kurikulum 2013 - Yuniar Adhinaya Yulianti; Dwi Wulandari (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
This study aims to analyze the suitability of the 21st-century learning methods, namely the flipped classroom method with the curriculum applied in Indonesia, the 2013 curriculum. The method used in this research is qualitative with a literature review as a data technique. Data collection was carried out by reviewing the relevant literature as the primary object. This study using descriptive qualitative analysis techniques. From the result of the literature study, it can be concluded that learning reverses the class according to the principles of learning in the 2013 curriculum. This can be seen from its application which is more student-centered. Besides, warning activities, asking questions, gathering information, associating and analyzing, and communicating can be implemented in flipped classroom learning based on the application of technology in it, so that students will have skills according to the 21st century.